Exploring user-generated content related to vegetarian customers in restaurants: An analysis of online reviews - Bai, Shizhen; Zheng, Xuezhen; Han, Chunjia; Bi, Xinrui (Frontiers in Psychology, 2023)
The purpose of this research was to explore and evaluate factors that impact the dining experience of vegetarian consumers within a range of vegetarian-friendly restaurants. To explore the factors and understand consumer experience, this study analyzed a vast number of user-generated contents of vegetarian consumers which have become vital sources of consumer experience information. This study utilized machine learning techniques and traditional methods to examine 54,299 TripAdvisor reviews of approximately 1,008 vegetarian-friendly restaurants in London. The study identified 21 topics that represent a holistic opinion influencing the dining experience of vegetarian customers. The results suggested that “value” is the most popular topic, and had the highest topic percentage. The results of regression analyses revealed that five topics had a significant impact on restaurant ratings, while twelve topics had negative impacts. Restaurant managers who pay close attention to vegetarian aspects may utilize the findings of this paper to satisfy vegetarian consumer requirements better and enhance service operations.